Ferrimagnetism and spin excitation in a Ni-Mn partially inverted spinel prepared using a modified polymeric precursor method - Ferreira, Rafael A. [UNESP]; Tedesco, Julio C. G.; Birk, Jonas O.; Kalceff, Walter; Yokaichiya, Fabiano; Rasmussen, Nina; Pena, Octavio; Henry, Paul F.; Simeoni, Giovanna G.; Bordallo, Heloisa N.; Lisboa Filho, Paulo Noronha [UNESP] (Elsevier B.V., 2014)
We demonstrate that a Ni-Mn oxide partially inverted spinel (Ni1-pMnv)[NivMn2-v]O-4 having inversion degree v approximate to 0.8 and produced by a modified polymeric precursor method exhibits behaviour previously reported only in monophased samples. The structure of the specimen was determined using Rietveld analysis of X-ray and neutron powder diffraction data, showing that at room temperature the material crystallizes in the Fd3(over bar)m space group with a lattice constant a = 8.392 angstrom. Combining magnetization measurements with neutron powder diffraction, we show that the magnetic structure of this spinel is associated with the interplay between the ferromagnetic and antiferromagnetic lattices which coexist due to the cations' presence on both tetrahedral and octahedral sites. Our analysis of the neutron diffraction data confirms the postulated magnetic structure involving a star-like moment arrangement, arising from competition for the B (octahedral) spinel sites by the Ni and Mn cations. Finally, we show that strong magnetic fluctuations are observed in the inelastic neutron scattering data. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; Chemical synthesis; X-ray scattering; Neutron scattering and diffraction; Rietveld analysis; Magnetic structures